# Thursday November 7th ## Projective Modules **Definition:** A **projective** module $P$ over a ring $R$ is an $R\dash$module such that the following diagram commutes: ```{=latex} \begin{center} \begin{tikzcd} & & P \arrow[dd, "f"] \arrow[lldd, "\exists \phi", dashed] \\ & & \\ M \arrow[rr, "g"] & & N \end{tikzcd} \end{center} ``` i.e. for every surjective map $g:M \surjects N$ and every map $f: P \to N$ there exists a lift $\phi: P \to M$ such that that $g \circ \phi = f$. **Theorem**: Every free module is projective. *Proof:* Suppose $M \surjects N \to 0$ and $F \mapsvia{f} N$, so we have the following situation: ```{=latex} \begin{center} \begin{tikzcd} & & x \arrow[d, hook] \arrow[llddd, dotted] & & \\ & & F \arrow[dd, "f"] \arrow[lldd, "\exists \phi", dashed] & & \\ & & & & \\ M \arrow[rr, "g", two heads] & & N \arrow[rr, dotted] & & 0 \end{tikzcd} \end{center} ``` For every $x\in X$, there exists an $m_x \in M$ such that $g(m_x) = f(i(x))$. By freeness, there exists a $\phi: F \to M$ such that this diagram commutes. $\qed$ **Corollary:** Every $R\dash$module is the homomorphic image of a projective module. *Proof:* If $M$ is an $R\dash$module, then $F \surjects M$ where $F$ is free, but free modules are surjective. $\qed$ **Theorem:** Let $P$ be an $R\dash$module. Then TFAE: a. $P$ is projective. b. Every SES $0 \to M \to N \to P \to 0$ splits. c. There exists a free module $F$ such that $F = P \oplus K$ for some other module $K$. *Proof:* $a \implies b$: We set up the following situation, where $s$ is produced by the universal property: ```{=latex} \begin{center} \begin{tikzcd} & & & P \arrow[d, "\id", two heads, hook] \arrow[ld, "\exists s"] & \\ 0 \arrow[r] & M \arrow[r] & N \arrow[r, two heads] & P \arrow[r] & 0 \end{tikzcd} \end{center} ``` $\qed$ $b \implies c$: Suppose we have $0 \to M \to N \to P \to 0$ a SES which splits, then $N \cong M \oplus P$ by a previous theorem. $\qed$ $c\implies a$: We have the following situation: ```{=latex} \begin{center} \begin{tikzcd} & & F = P \oplus K \arrow[dd, "\pi", bend right] \arrow[lldddd, "\exists h", dotted] \\ & & \\ & & P \arrow[uu, "\iota", bend right] \arrow[dd, "f"] \arrow[lldd, "\phi = \iota \circ h", dotted] \\ & & \\ M \arrow[rr, two heads] & & N \end{tikzcd} \end{center} ``` By the previous argument, there exists an $h: F\to M$ such that $g\circ h = f \circ \pi$. Set $\phi = h\circ \iota$. *Exercise*: Check that $g\circ \phi = f$. $\qed$ **Theorem:** $\bigoplus P_i$ is projective $\iff$ each $P_i$ is projective. *Proof:* $\implies$: Suppose $\oplus P_i$ is projective. Then there exists some $F = K \oplus \bigoplus P_i$ where $F$ is free. But then $P_i$ is a direct summand of $F$, and is thus projective. $\impliedby$: Suppose each $P_i$ is projective. Then there exists $F_i = P_i \oplus K_i$, so $F \definedas \bigoplus F_i = \bigoplus (P_i \oplus K_i) = \bigoplus P_i \oplus \bigoplus K_i$. So $\bigoplus P_i$ is a direct summand of a free module, and thus projective. $\qed$ > Note that a direct sum has *finitely many* nonzero terms. Can use the fact that a direct sum of free modules is still free by taking a union of bases. *Example of a projective module that is not free:* Take $R = \ZZ_6$, which is not a PID and not a domain. Then $\ZZ_6 = \ZZ_2 \oplus \ZZ_3$, and $\ZZ_2, \ZZ_3$ are projective $R\dash$modules. By previous statements, we know these are torsion as $\ZZ\dash$modules, and thus not free. ## Endomorphisms as Matrices > See section 7.1 in Hungerford Let $M_{m, n}(\RR)$ denote $m\times n$ matrices with coefficients in $R$. This is an $R\dash R$ bimodule, and since $R$ is not necessarily a commutative ring, these two module actions may not be equivalent. If $m=n$, then $M_{n,n}(R)$ is a ring under the usual notions of matrix addition and multiplication. **Theorem:** Let $V, W$ be vector spaces where $\dim V = m$ and $\dim W = n$. Let $\hom_k(V, W)$ be the set of linear transformations between them. Then $\hom_k(V, W) \cong M_{m, n}(k)$ as $k\dash$vector spaces. *Proof:* Choose bases of $V, W$. Then consider \begin{align*} T: V \to W \\ v_1 \mapsto \sum_{i=1}^n a_{1, i} ~w_i \\ v_2 \mapsto \sum_{i=1}^n a_{2, i} ~w_i \\ \vdots \end{align*} This produces a map \begin{align*} f: \hom_k(V, W) &\to M_{m, n}(k) \\ T &\mapsto (a_{i, j}) ,\end{align*} which is a matrix. > *Exercise: Check that this is bijective.* $\qed$ **Theorem:** Let $M, N$ be free left $R\dash$modules of rank $m, n$ respectively. Then $\hom_R(M, N) \cong M_{m, n}(R)$ as $R\dash R$ bimodules. *Notation:* Suppose $M, N$ are free $R\dash$modules, then denote $\beta_m, \beta_n$ be fixed respective bases. We then write $[T]_{\beta_m, \beta_n} \definedas (a_{i, j})$ to be its *matrix representation*. **Theorem**: Let $R$ be a ring and let $V, W, Z$ be three free left $R\dash$modules with bases $\beta_v, \beta_w, \beta_z$ respectively. If $T: V \to W, S: W\to Z$ are $R\dash$module homomorphisms, then $S \circ T: V \to Z$ exists and $$ [S \circ T]_{\beta_v, \beta_z} = [T]_{\beta_v, \beta_w} [S]_{\beta_w, \beta_z} $$ *Proof:* Exercise. Show that $$ (S \circ T)(v_i) = \sum_j^t \sum_k^m a_{ik} b_{kj} z_j .$$ $\qed$ ## Matrices and Opposite Rings Suppose $\Gamma: \hom_R(V, V) \to M_n(R)$ and $V$ is a free left $R\dash$module. By the theorem, we have $\Gamma(T \circ S) = \Gamma(S) \Gamma(T)$. We say that $\Gamma$ is an **anti-homomorphism**. To address this mixup, given a ring $R$ we can define $R^{op}$ which has the same underlying set of $R$ but with the modified multiplication $$ x \cdot y \definedas yx \in R .$$ If $R$ is commutative, then $R \cong R^{op}$. $\qed$ **Theorem**: Let $R$ be a unital ring and $V$ an $R\dash$module. Then $\hom_R(V, V) \cong M_n(R^{op})$ as rings. *Proof*: Since $\Gamma(S \circ T) = \Gamma(T) \Gamma(S)$, define a map \begin{align*} \Theta: M_{n, n}(R) &\to M_{n, n}(R^{op}) \\ A &\mapsto A^t .\end{align*} Then $$ \Theta(AB) = (AB)^t = B^t A^t = \Theta(B) \Theta(A) ,$$ so $\Theta$ is an anti-isomorphism. Thus $\Theta\circ \Gamma$ is an anti-anti-homomorphism, i.e. a usual homomorphism. $\qed$ **Definition:** A matrix $A$ is **invertible** iff there exists a $B$ such that $AB = BA = \id_n$. **Proposition:** Let $R$ be a unital ring and $V, W$ free $R\dash$modules with $\dim V = n, \dim W = m$. Then 1. $T \in \hom_R(V, W)$ is an isomorphisms iff $[T]_{\beta_v, \beta_w}$ is invertible. 2. $[T\inv]_{\beta_v, \beta_w} = [T]_{\beta_v, \beta_w}\inv$. **Definition:** We'll say that two matrices $A, B$ are **equivalent** iff there exist $P, Q$ invertible such that $PAQ = B$.